Breast cancer survival and the health system in Brazil: an analysis of public and private healthcare - Ferreira, Adriana de Souza Sérgio; Cintra, Jane Rocha Duarte; Fayer, Vívian Assis; Nogueira, Mário Círio; Júnior, Cassimiro Baesso; Bustamante-Teixeira, Maria Teresa; Chaoubah, Alfredo; Cintra, Arthur Duarte; Simão, Caroline Montes; Guerra, Maximiliano Ribeiro (Frontiers in Oncology, 2023)
Background The incidence of breast cancer is increasing globally; however, survival outcomes vary and are lower in developing countries. Methods We analyzed the 5- and 10-year survival rates for breast cancer according to the type of healthcare insurance (public vs. private) in a referral center for cancer care in the Brazilian southeast region. This hospital-based cohort study included 517 women diagnosed with invasive breast cancer between 2003 and 2005. The Kaplan–Meier method was used to estimate the probability of survival, and the Cox proportional hazards regression model was used to assess prognostic factors. Results The 5- and 10-year breast cancer survival rates were as follows: private healthcare service survival rate of 80.6% (95% CI 75.0–85.0) and 71.5% (95% CI 65.4–77.1), respectively, and public healthcare service survival rate of 68.5% (95% CI 62.5–73.8) and 58.5% (95% CI 52.1–64.4), respectively. The main factors associated with the worst prognosis were lymph node involvement in both healthcare services and tumor size >2 cm only in public health services. The use of hormone therapy (private) and radiotherapy (public) was associated with the best survival rates. Conclusions The survival discrepancies found between health services can be explained mainly by the difference in the stage of the disease at the time of diagnosis, indicating inequalities in access to the early detection of breast cancer.